Konsep Komunikasi Pendidikan dalam Alqur`An Surat Lukman - Ahmad Gawdy Prananosa; Donni Pestalozi; Adisel Adisel (Journal Of Administration and Educational Management (ALIGNMENT), 2018)
This study aims to examine the concept of educational communication in the Qur'an Lukman letter. This research was designed using a qualitative approach by applying library research methods. The data used in this study are sourced from primary data and secondary data, while the primary data are Al-Qur`an Letters Lukman and supported by the Prophet's traditions that are relevant to the research problem, while secondary data are sourced from books, magazines and written documents. The conclusion of this research reveals that the concept of educational communication in Lukman's Letter is indicated by the dialogical atmosphere between father and son in an effort to achieve life safety in the world and the hereafter. The term dialogic here shows that there is an element of communication between two people, in this case father and son. My father is a communicator or idea initiator in planning the dialogue atmosphere. At the same time it is the party that listens (in dialogue feedback) so that it also becomes the communicant. Keywords: Educational Communication, Al-qur`an Surat Lukman